Analytical Mechanics of Magnetic Particles Suspended in Magnetorheological Fluid - Hanmant Salunkhe; Surendra Thikane (International Journal of Engineering and Management Research, 2022)
In this paper, the behavior of MR particles has been systematically investigated within the scope of analytical mechanics. . A magnetorheological fluid belongs to a class of smart materials. In magnetorheological fluids, the motion of magnetic particles is controlled by the action of internal and external forces. This paper presents analytical mechanics for the interaction of system of particles in MR fluid. In this paper, basic principles of Analytical Mechanics are utilized for the construction of equations.